Employee performance measures appraised by training and labor market: Evidence from the banking sector of Germany - Naveed Ahmad Khan; Andrija Mihoci; Silke Michalk; Kirill Sarachuk; Hafiz Ali Javed (Administrative Sciences, 2022)
Our paper examines the impact of training outputs and employment factors on several facets of employee performance while supporting managerial decision-making in the banking sector. First, we introduce four performance measures in individual productivity assessment. Second, three identified groups of covariates are associated with these measures, namely, the training method success, delivery of knowledge, and labor market performance feedback. Based on our empirical results from Germany, we suggest that response-related decisions are accompanying bank employees' profiles and appraisal. In particular, we form decision-making functions and finally show that the banking industry successfully balances between internal and external factors in optimizing employees' performance.
Keywords: 350; banking industry; cross-sectional dependence; employee performance; labor market environment; performance measures; training programs